How to kiss a cowboy - Kennedy, Joanne (Kennedy, Joanne. Cowboys of Decker Ranch, 2015)
Winning comes naturally to bronc rider Brady Caine. Ruggedly handsome, careless, and charismatic, he's riding high when he lands an endorsement deal with Lariat Western Wear that pairs him up with champion barrel racer Suze Carlyle. Brady and Suze couldn't be more different, but that only lights up their attraction. A stupid move on Brady's part lands Suze in the hospital, her career in tatters. Now it's a whole new game for both of them. Brady is desperate to help Suze rebuild her life, but he's the last person she wants around. Suze's got plenty of grit and determination, but learning to trust Brady again will take a very different kind of courage. This is the cowboy story you've been waiting for.